(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aimed to find out the leadership of Village Head in increasing community participation in development in Balle Village, Kahu District, Bone Regency. This study used a qualitative method. Data collection was carried out by using observation, interviews and documentation techniques. The results showed that the leadership of the Village Head in Increasing Community Participation in Development in Balle Village, Kahu District, Bone Regency was still not optimal, while for Community Participation, there were still many people who did not have awareness and willingness when viewed from aspects 1) Motivator, the village head needed skill to improve in giving motivation. The village head motivated his subordinates to develop talent, the ability to create a better village office in carrying out all the tasks given by the balle village head. 2) Facilitator, considered optimal in facilitating development activities. the village head had provided facilities and infrastructure for the community and village officials to facilitate the development of the village of Balle. 3) Mobilizers were good because they do something related to development for the public interest, the village head always encouraged the community and government officials to actively participated in implementing village development.